2009
DOI: 10.1111/j.1471-4159.2008.05861.x
|View full text |Cite
|
Sign up to set email alerts
|

AZD2184: a radioligand for sensitive detection of β‐amyloid deposits

Abstract: The presence of β‐amyloid plaques in brain is a hallmark of Alzheimer’s disease (AD) and serves as a biomarker for confirmation of diagnosis postmortem. Positron emission tomography (PET) radioligands such as Pittsburgh compound B ([11C]‐2‐(3‐fluoro‐4‐methylamino‐phenyl)‐benzothiazol‐6‐ol) (PIB) binds selectively to β‐amyloid and are promising new tools supporting the clinical diagnoses of AD. In addition, such methodology may be useful for evaluation of new drugs aiming at reduction of amyloid plaque load. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
112
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(117 citation statements)
references
References 22 publications
4
112
1
Order By: Relevance
“…Fifteen micrometer thick sections were serially cut using a cryostat. The histochemistry staining of AD brain sections with CR-BSA-(Gd-DTPA)n was improved stepwise in the experiment according the staining method of the traditional CR dye (Schmidt et al, 2001;Johnson et al, 2009). The process was stopped by immersion in distilled water.…”
Section: Synthesis Of Bsa-(gd-dtpa)nmentioning
confidence: 99%
“…Fifteen micrometer thick sections were serially cut using a cryostat. The histochemistry staining of AD brain sections with CR-BSA-(Gd-DTPA)n was improved stepwise in the experiment according the staining method of the traditional CR dye (Schmidt et al, 2001;Johnson et al, 2009). The process was stopped by immersion in distilled water.…”
Section: Synthesis Of Bsa-(gd-dtpa)nmentioning
confidence: 99%
“…About a decade ago, the first successful Aβ plaque-specific PET imaging study was conducted in a living human subject clinically diagnosed with probable AD using the 74 It is clear that this type of PrP diagnostics related diseases has a great potential to be further developed and new imaging assays are still being looked for. Some of them could be based on quantum dots (QDs).…”
Section: Scmentioning
confidence: 99%
“…[4][5][6][7] The development of amyloid-specific imaging agents is generally based on conjugated dyes, such as Congo red, Chrysamine G, and thioflavin-T, which have been used in fluorescent staining of plaques and tangles in postmortem AD brain sections. Several radioligands for positron emission tomography (PET) and single photon emission computerized tomography (SPECT), including [ (2-[6-(methylamino)pyridin-3-yl]-1,3-benzothiazol-6-ol), 12 [ 17,18 and [ 19 have been tested in clinical trials and demonstrated the potential utility as in vivo imaging agents for Aβ plaque deposition in the living human brain (Figure 1).…”
Section: -3mentioning
confidence: 99%